Efektivitas Expressive Writing dalam Meningkatkan Self-Esteem Pecandu Narkoba di Program Rehabilitasi BNN Baddoka - Nurul Utami Safaruddin; Sitti Murdiana; Ahmad Ridfah (Universitas Islam Indonesia, 2020)
Low self-esteem is one of the problems that causes individual drugging. Expressive writing is one of the interventions that is able to influence self-esteem improvement on drug addicts. This research aimed to figure out the effectivity of expressive writing in improving self-esteem of drug addicts at rehabilitation of BNN Baddoka. It applied quasy experimental design, one-group pretest-postest design. The research subject were 8 drug addicts with low and medium self-esteem. Self-esteem scale was used as the research measurement adopted from Widyastuti (2002) with realibility of 0.992. The data were analyzed using Wilcoxon nonparametrical statistic test. The result reveals that expressive writing improved self-esteem of drug addicts at rehabilitation program of BNN Baddoka, the increase was seen from the significant difference between self-esteem score when pretest with posttest (W = 2, mean pretest = 11,625, mean posttest = 14,625, p = 0.026). Of the eight subjects, six of them experienced an increase in score, one subject decreased the score, and one subject did not change the score. Expressive writing can be used to improve self-esteem of drug addicts, so it can also be given in rehabilitation program